Tumor tissue samples collection for scientific research in morphology and molecular oncology - O. R. Khabarov; B. D. Seferov; K. A. Aliev; D. V. Zima; E. P. Golubinskaya; E. Yu. Zyablitskaya (Исследования и практика в медицине, 2024)
Purpose of the study. Is to describe the experience of creating a collection of biological images of tumor tissues and biomaterials, which are control samples, for scientific research in morphology and molecular oncology.Materials and methods. We studied the molecular markers of cell cycle regulation, apoptosis, oncogenesis and angiogenesis, the expression of proteins that regulate inflammation and tumor infiltrate cells in biocollections of verified tumors of common localizations: e. g. thyroid cancer, colorectal cancer, breast cancer, prostate adenocarcinoma, endometrioid adenocarcinoma. Also, tissue fragments with normal structure or non-tumor pathology (autoimmune thyroiditis, adenomatous and thyrotoxic goiter, benign formations of the colon, fibrocystic disease of the mammary glands, benign prostatic hyperplasia, endometrial hyperplasia) were used as control samples or comparison groups. The total number of tissue samples is n = 7000.Results. It is reasonable to gather the collection in a pathomorphological laboratory according to the profile of the medical institutions, which has a sufficient volume of incoming target material and specialized morphologists to verify tumors of a given localization. It is necessary to consider the regional and ethnic specifics of the population, which determines the sampling and mutational load. The laboratory must initiate an addition to the informed consent of patients about the possibility of conducting morphological and molecular genetic studies for scientific purposes and publishing their results in a depersonalized form for the development of new elaborations, when signing the contracts with legal entities and individuals and when serving patients within an institution. When working with biocollections, it has to consider having registers of tissue biomaterials of target disorder groups of main localizations with downloading by year from an accessible information system, consider external factors affecting the database (changes in clinical recommendations and classifications, the population of patients served, pandemics and other significant events). The standard of the preanalytical stage, data collection, development of protocols for analytical molecular genetic studies and their evaluation, the utilization of the capabilities of working with reagents for scientific tasks and modeling experiments on laboratory animals are crucial.Conclusion. The formed biocollection made it possible to carry out a number of initiative and funded domestic and international scientific projects at the request of clinicians and fundamental researchers, as well as to improve the quality standards of morphological and molecular genetic oncology diagnostics. Biobanking makes the pathological archive more accessible for review and use, significantly expanding its scientific and practical potential. Scientific and medical research do not conflict and can be used within the same laboratory.